To defer or differ: Experimental evidence on the role of cash transfers on Nigerian couples’ decision-making - Bakhtiar, M. Mehrab; Fafchamps, Marcel; Goldstein, Markus; Leonard, Kenneth L.; Papineni, Sreelakshmi (International Food Policy Research Institute, 2024)
We conduct an original lab-in-the-field experiment on the decision–making process of married couples over the allocation of rival and non-rival household goods. The experiment measures individual preferences over allocations and traces the process of deferral, consultation, communication and accommodation by which couples implement these preferences. We find few differences in individual preferences over allocations of goods. However, wives and husbands have strong preferences over process: women prefer to defer decisions to their husbands even when deferral is costly and is not observed by the husband; men rarely defer under any condition. Our study follows a randomized controlled trial that ended a year earlier and gave large cash transfers over eighteen months to half of the women in the study. We estimate the effect of treatment on the demand for agency among women and find that the receipt of cash transfers does not change women’s bargaining process except in a secret condition when the decision to defer is shrouded from her husband. This suggests that the cash transfer to women increases their demand for agency but does not change the intra-household balance of power enough to allow them to express it publicly.